2011
DOI: 10.1186/1476-0711-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of redox-active benzaldehydes that target cellular antioxidation

Abstract: BackgroundDisruption of cellular antioxidation systems should be an effective method for control of fungal pathogens. Such disruption can be achieved with redox-active compounds. Natural phenolic compounds can serve as potent redox cyclers that inhibit microbial growth through destabilization of cellular redox homeostasis and/or antioxidation systems. The aim of this study was to identify benzaldehydes that disrupt the fungal antioxidation system. These compounds could then function as chemosensitizing agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 74 publications
2
49
0
Order By: Relevance
“…In addition, several reports document the possibility of enhancing the fungicidal activity of ROS-inducing antifungals by targeting the oxidative stress response system of fungi. For example, Kim and coworkers demonstrated that different redox-potent chemosensitizing agents like natural dihydroxybenzaldehydes, thymol, or salicylaldehyde could enhance the antifungal activity of different ROS-inducing antifungals [2729]. One of their studies specifically demonstrates that chemically targeting the oxidative stress response system of fungi effectively augments antimycotic potency of AmB [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several reports document the possibility of enhancing the fungicidal activity of ROS-inducing antifungals by targeting the oxidative stress response system of fungi. For example, Kim and coworkers demonstrated that different redox-potent chemosensitizing agents like natural dihydroxybenzaldehydes, thymol, or salicylaldehyde could enhance the antifungal activity of different ROS-inducing antifungals [2729]. One of their studies specifically demonstrates that chemically targeting the oxidative stress response system of fungi effectively augments antimycotic potency of AmB [28].…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophobic nature of thymol allows it to interact with lipids found in the cell and in mitochondrial membranes. In addition, thymol is a redox inhibitor that interferes with electron transport similar to vanilloids thereby inducing apoptosis . Accordingly, studies of thymol in B16 melanoma cells show that thymol cytotoxicity is reversible with the addition of vitamin C or vitamin E .…”
Section: Discussionmentioning
confidence: 99%
“…Administration of novel antifungals or alternative adjunctive therapeutic agents (such as EOs) represents a possible solution [11]. EOs or their constituents may be used as monotherapy, but in combination with conventional drugs a more improved antifungal efficacy could be reached [12]. Beyond the improved antifungal activity, the dosage of antifungals and their side effects could be diminished and the emergence of resistance to them could be delayed [13].…”
Section: Eceomentioning
confidence: 99%